The potential impact of Trans-Pacific Partnership Agreement (TPPA) on Malaysia's access to medicine - Alavi, Rokiah; Mohd Amin, Ruzita; Mat Ghani, Gairuzazmi; Idris, Rafiq (2015)
Trans-Pacific Partnership Agreement (TPPA) negotiation opens door of opportunities as well as challenges to Malaysia. The key concern is the involvement of the US which is feared to bring in many WTOPlus commitments in the agreement, even though the TPPA may help to provide significant market in terms of penetrating to the US huge market. Many provisions are speculated as to be introduced in the TPPA and would bring detrimental impact on a country’s economy. This study focuses on one issue in relation to Malaysia’s participation in TPPA. Issue on the potential impact of TRIPS-Plus provision in the intellectual property chapter on access to medicine in Malaysia is being examined. TRIPS-Plus provisions would have significant impact on access to medicines as well as on the domestic pharmaceutical industry. So far there are no studies that have systematically evaluated the impact of TRIPS-Plus agreement on these issues in Malaysia. This study uses Macroeconomic Model of Impact Changes in Intellectual Property Rights (MICIPR) to assess the impact of TPPA on Malaysia’s access to medicine by examining the impact of data exclusivity, patent term restoration and patent linkages provisions on medicine price, medicine expenditure and the sales’ of domestic pharmaceutical industry.